The Bernese peri-acetabular osteotomy through a modified approach. A technical note - Whittingham-Jones, Paul (Springer Berlin Heidelberg, 2013)
INTRODUCTION: A modification of the technique for performing the Bernese periacetabular osteotomy is described. MATERIALS AND METHODS: A medial approach to the Ischium and a subtle re-orientation of the pubic osteotomy are detailed. CONCLUSION: Surgical morbidity is likely decreased with a concurrent cosmetic advantage without compromise to surgical correction or patient safety.